Antimicrobial and Antioxidant Activities of Resins and Essential Oil From Pine (Pinus merkusii, Pinuso ocarpa, Pinus insularis) and Agathis (Agathis loranthifolia) - Mardho Tillah; Irmanida Batubara; Rita Kartika Sari (Biosaintifika: Journal of Biology & Biology Education, 2017)
The most common human pathogen that colonizes in a third of healthy people around the world are Staphylococcus aureus, and one of the materials allegedly able to overcome the pathogen is resin. Resin has been used in folk medicine for thousands of years to treat diseases. The antimicrobial activity of natural resins can be associated with a variety of organic compounds contained in them such as diterpenoids and triterpenoids. This research aimed to explore the antibacterial and antioxidant activities of Pinus merkusii, P. oocarpa, P. insularis, Agathis loranthifolia resins and essential oil. Resin was separated by distillation process to get essential oil and the residue was extracted using n-hexane, ethyl acetate (EtOAc), and methanol (MeOH). Antioxidant activity was performed by DPPH (1,1diphenyl-2-picryl hydrazyl) radical scavenging method. The antibacterial activity of resins and essential oil of the samples determined using the disc diffusion method against Staphylococcus aureus and Escherichia coli. The results showed that the yield of resin extract was ranging from 8.44 % to 95.56%. All extracts and essential oil could not inhibit E coli growth but inhibit the S. aureus growth. This experiment concluded that resin n-hexane extract from P.oocarpa was the most potent as antibacterial activity against S. aureus. All of the samples used had less potential antioxidant activity compared to positive control ascorbic acid. Result of this study show that pine resin from Indonesia has potential as an antibacterial agent.